A Novel Risk Scoring Tool to Predict Saphenous Vein Graft Occlusion After Cardiac Artery Bypass Graft Surgery - Cheng, Yujing; Ma, Xiaoteng; Liu, Xiaoli; Zhao, Yingxin; Sun, Yan; Zhang, Dai; Zhao, Qi; Xu, Yingkai; Zhou, Yujie (Frontiers in Cardiovascular Medicine, 2021)
Obejectives: Coronary artery bypass grafting (CABG) success is reduced by graft occlusion. Understanding factors associated with graft occlusion may improve patient outcomes. The aim of this study was to develop a predictive risk score for saphenous vein graft (SVG) occlusion after CABG. Methods: This retrospective cohort study enrolled 3716 CABG patients from January 2012 to March 2013. The development cohort included 2477 patients and the validation cohort included 1239 patients. The baseline clinical data at index CABG was analyzed for their independent impact on graft occlusion in our study using Cox proportional hazards regression. The predictive risk scoring tool was weighted by beta coefficients from the final model. Concordance (c)-statistics and comparison of the predicted and observed probabilities of predicted risk were used for discrimination and calibration. Results: A total of 959 (25.8%) out of 3716 patients developed at least one SVG occlusion. Significant risk factors for occlusion were male sex, diabetes, smoking (currently), hyperuricemia, dyslipidemia, prior percutaneous coronary intervention (PCI), a rising number of lesion vessels, and SVG. On-pump surgery, and the use of angiotensin-converting enzyme inhibitors (ACEI)/angiotensin receptor blockers (ARB) and calcium channel blockers (CCB) were protective factors. The risk scoring tool with 11 variables was developed from the derivation cohort, which delineated each patient into risk quartiles. The c-statistic for this model was 0.71 in the validation cohort. Conclusions: An easy-to-use risk scoring tool that used common clinical variables was developed and validated. The scoring tool accurately estimated the risk of late SVG occlusion after CABG.